2006
DOI: 10.1139/x05-251
|View full text |Cite
|
Sign up to set email alerts
|

Tree species diversity reduces the invasibility of maritime pine stands by the bast scale, Matsucoccus feytaudi (Homoptera: Margarodidae)

Abstract: Species-rich plant communities may be more resistant to invasive herbivores because of reduced host-plant accessibility and increased natural enemy diversity and abundance. We tested these hypotheses in Corsica, a Mediterranean island recently invaded by the maritime pine bast scale, Matsucoccus feytaudi Duc., which causes widespread tree mortality in Pinus pinaster Ait. The endemic Matsucoccus pini Green infests Corsican pine, Pinus nigra laricio Poiret, where it is controlled by the native predatory bug Elat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 26 publications
2
50
0
3
Order By: Relevance
“…However, most stand-scale studies involved native insects, and there is comparatively little information on invasions by non-native insects. Two studies in Europe have shown negative relationships between tree species richness and the abundance of invasive tree-feeding insects at the plot or stand scale (Jactel et al 2006;Guyot et al 2015). Conversely, in the USA, a positive relationship between native tree species richness and the number of successful invasions by non-native tree-feeding insects was observed (Liebhold et al 2013), although that study assessed larger-scale county-level data that are not directly comparable with plot-level data.…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 93%
See 1 more Smart Citation
“…However, most stand-scale studies involved native insects, and there is comparatively little information on invasions by non-native insects. Two studies in Europe have shown negative relationships between tree species richness and the abundance of invasive tree-feeding insects at the plot or stand scale (Jactel et al 2006;Guyot et al 2015). Conversely, in the USA, a positive relationship between native tree species richness and the number of successful invasions by non-native tree-feeding insects was observed (Liebhold et al 2013), although that study assessed larger-scale county-level data that are not directly comparable with plot-level data.…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 93%
“…This states that more diverse forests can provide more diverse and abundant feeding and nesting resources for insect predators and parasitoids, thus increasing their capacity to control populations of prey (i.e., insect herbivores). Although an increasing body of evidence supports a positive correlation between tree diversity and natural enemy diversity (Castagneyrol and Jactel 2012;Staab et al 2014), the actual contribution of predators to the top-down control of pest insects in mixed forests remains difficult to demonstrate (Jactel et al 2006;Muiruri et al 2016).…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 99%
“…Forest insects (e.g. Matsucoccus feytaudi, Jactel et al, 2006) and pathogens that are passively wind dispersed have a lower chance of landing on the appropriate host tree in mixed stands (Heybroek, 1982). Several tree diseases (such as H. annosum) spread through root contacts and the presence of non-host trees may limit this process (Linden and Vollbrecht, 2002).…”
Section: Stand Compositionmentioning
confidence: 99%
“…Although the opposite pattern-associational susceptibility (AS)-can also be observed (White and Whitham 2000;Schuldt et al 2015), AR seems a more common phenomenon in forest ecosystems (Jactel and Brockerhoff 2007;Castagneyrol et al 2014a; but see Kambach et al 2016). AR has been described mainly for native pest species but it can be hypothesized that similar mechanisms are involved for invasive pests (Jactel et al 2006;Guyot et al 2015).…”
Section: Introductionmentioning
confidence: 99%